Tutorial: Development and Implementation of a Multidisciplinary Preoperative Nutrition Optimization Clinic. Issue 7 (31st March 2020) - Williams, David G. A.; Villalta, Elizabeth; Aronson, Solomon; Murray, Sutton; Blitz, Jeanna; Kosmos, Virginia; Wischmeyer, Paul E.; ,
Abstract: Although much is known about surgical risk, little evidence exists regarding how best to proactively address preoperative risk factors to improve surgical outcomes. Preoperative malnutrition is a widely prevalent and modifiable risk factor in patients undergoing surgery. Malnutrition prior to surgery portends significantly higher postoperative mortality, morbidity, length of stay, readmission rates, and hospital costs. Unfortunately, perioperative malnutrition is poorly screened for and remains largely unrecognized and undertreated—a true "silent epidemic" in surgical care. To better address this silent epidemic of surgical nutrition risk, here we describe the rationalization, development, and implementation of a multidisciplinary, registered dietitian–driven, preoperative nutrition optimization clinic program designed to improve perioperative outcomes and reduce cost. Implementation of this novel Perioperative Enhancement Team (POET) Nutrition Clinic required a collaboration among many disciplines, as well as an identified need for multidimensional scheduling template development, data tracking systems, dashboard development, and integration of electronic health records. A structured malnutrition risk score (Perioperative Nutrition Screen score) was developed and is being validated. A structured malnutrition pathway was developed and is under study. Finally, the POET Nutrition Clinic has established a novel role for a perioperative registered dietitian as the integral point person to deliver perioperative nutrition care. We hope this structured model of perioperative nutrition assessment and optimization will allow for wide implementation and generalizability in other centers worldwide to improve recognition and treatment of perioperative nutrition risk.